Determining payments for watershed services by hydro-economic modeling for optimal water allocation between agricultural and municipal water use - Haavisto, R. (2019)
Ever growing demand for agricultural and municipal water, caused by population growth and the need to feed the world, as well as increasing stress over waterbodies crave for efficient and sustainable water management. Especially in areas where municipal and agricultural water consumption rely on the same water sources for satisfying their water needs, it is important to explore evidence-based policy instruments that achieve sustainable water use in a way that is optimal for both dwellers and farmers concurrently. Some economists regard market-based policy instruments superior to command-and-control instruments in enhancing the economically efficient use of natural resources [1,2]. While some clearly favor market-based instruments in ecosystem management [3,4], such instruments are not the dominant policy strategy for environmental protection [5]. Instead, many authors call for hybrid instruments that combine market-based and command-and-control strategies [5,6]. According to Vatn [7], command-and-control is essential for the functioning of ecosystem markets. Muradian and Rival [5] argue that hybrid regimes that combine command-and-control, market based tools and community-based institutional arrangements are more suitable in managing ecosystem services—which so often raise challenges due to their common good character and intrinsic complexity—than pure markets or hierarchies.